Penguatan Kerjasama antara Chiba Islamic Culture Center (CICC) dan Universitas PTIQ dalam Pengembangan Ekonomi Syariah Berbasis Komunitas: (Strategi Awal dan Implikasi Praktis) - Imron Natsir (STIKes Ibnu Sina Ajibarang, 2025)
Collaboration between international organisations and educational institutions plays a strategic role in developing an inclusive and sustainable Islamic economy. The Chiba Islamic Culture Centre, as a community-based organisation in Japan, and PTIQ University, as an Islamic educational institution in Indonesia, have great potential to integrate Islamic values into the development of a Sharia-based economy. This article aims to initiate and strengthen cooperation between these two institutions, focusing on community empowerment through an Islamic economic approach. The methodology employed utilises a qualitative descriptive approach, incorporating data collection techniques such as interviews, observations, and document reviews. The expected outcome is the establishment of a strategic cooperation model that can be practically implemented, covering empowerment programs based on zakat, waqf, and technology, as well as the formation of an Islamic economic ecosystem capable of improving the welfare of the target community. This article also identifies challenges and opportunities in program implementation, providing recommendations for the sustainability of this cross-border collaboration